A prospective, longitudinal study of the renin-angiotensin system, prostacyclin and thromboxane in the first trimester of normal human pregnancy: association with birthweight - Al Kadi, H; Nasrat, H; Broughton Pipkin, F (Human reproduction (Oxford), 2005)
Very early human pregnancy is a state of cardiovascular underfilling. The renin-angiotensin system (RAS) is directly concerned with sodium and water homeostasis. Angiotensinogen is known to be the rate-limiting component in the generation of angiotensin I, and hence angiotensin II, in pregnancy. The usual measurement of 'renin activity' does not differentiate between enzyme and substrate. We hypothesized that the RAS is activated from the start of pregnancy; plasma renin concentration (PRC) and angiotensinogen will show differential regulation and might stimulate the rise in prostacyclin. A prospective study of 12 nulliparous normal women. PRC and angiotensinogen and excretion of prostacyclin and thromboxane metabolites were measured pre-pregnancy and four to six times after conception to 13 weeks. By 6 weeks gestation, mean PRC was markedly raised and remained stable to 13 weeks. The initial angiotensinogen response varied, but rose consistently after 6-8 weeks. Regression analysis showed angiotensinogen in the first trimester to be strongly associated with corrected birthweight centile (P < 0.001). Excretion of eicosanoid metabolites was very variable, but rose significantly from 6 weeks; the ratio between prostacyclin and thromboxane excretion did not alter over this time. There was no correlation between the various hormones measured. Angiotensinogen is known to be rate-limiting in pregnancy. Its association with birthweight may be through effects on early plasma volume expansion and may have implications for intrauterine growth restriction and pre-eclampsia.